2016
DOI: 10.1038/srep35373
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Mannosylated DC-SIGN Ligands as Immunomodulants

Abstract: DC-SIGN, a C-type lectin mainly expressed by DCs, mediates antigen uptake and can induce specific immune responses, depending on the ligand involved. Owing to these properties, DC-SIGN is an attracting target for approaches aimed at tailoring the immune response towards specific immunologic outcomes. A multivalent DC-SIGN ligand (Polyman26), containing at its core a fluorescent “rod-like” spacer and able to inhibit DC-SIGN mediated HIV infection in nanomolar concentration, has been recently developed by our gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…DC/L-SIGN antagonists may help reducing the severity of SARS-CoV-2 infection by inhibiting the trans-receptor role played by these CLRs. We show here that was shown to induce a pro-inflammatory anti-viral response (Berzi et al, 2016), which should be beneficial at the onset of the infection and may help to steer the immune response towards a profile correlated with milder forms of the disease.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…DC/L-SIGN antagonists may help reducing the severity of SARS-CoV-2 infection by inhibiting the trans-receptor role played by these CLRs. We show here that was shown to induce a pro-inflammatory anti-viral response (Berzi et al, 2016), which should be beneficial at the onset of the infection and may help to steer the immune response towards a profile correlated with milder forms of the disease.…”
Section: Discussionmentioning
confidence: 81%
“…Polyman26 (PM26, Figure 6A) is a multivalent glycomimetic mannoside tailored for optimal interaction with DC-SIGN (Ordanini et al, 2015). It is known to bind DC-SIGN carbohydrate recognition domain (CRD), eliciting a Th-1 type response from human immature monocyte derived dendritic cells (Berzi et al, 2016). It also inhibits DC-SIGN mediated HIV infection of CD8 + T lymphocytes with an IC50 of 24 nM (Ordanini et al, 2015).…”
Section: Dc-sign Binding To the S Protein And Dc-sign-dependent Transmentioning
confidence: 99%
“…Flexible platforms that represent the targeting vector with self-adjuvant properties will be required as a basis to enable the possibility of personalized vaccines. Examples of such platforms, such as Clec9A-specific nanoemulsions, Lipovaxin and Polyman26, already exist [46,90,131]. Thus, only the substitution of necessary antigens will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Such particles were found to be neutral toward maturation and IL-10 production. Another approach is to use the so-called Polyman26, which is a glycodendrimer that includes a linear rigid spacer at its core [90]. It has been shown that Polyman26 was efficiently internalized by moDCs via DC-SIGN-mediated endocytosis and then routed to early endosomal and endolysosomal compartments.…”
Section: Dc-sign Receptor Targetingmentioning
confidence: 99%
See 1 more Smart Citation